2010
DOI: 10.1103/physrevd.81.126001
|View full text |Cite|
|
Sign up to set email alerts
|

Synchrotron radiation in strongly coupled conformal field theories

Abstract: Using gauge/gravity duality, we compute the energy density and angular distribution of the power radiated by a quark undergoing circular motion in strongly coupled N = 4 supersymmetric YangMills (SYM) theory. We compare the strong coupling results to those at weak coupling, and find the same angular distribution of radiated power, up to an overall prefactor. In both regimes, the angular distribution is in fact similar to that of synchrotron radiation produced by an electron in circular motion in classical elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
182
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(210 citation statements)
references
References 31 publications
28
182
0
Order By: Relevance
“…The second traceless condition allows us to simplify the right-hand side of Eq. (31). Moving The Ricci tensor quadratic in the first order metric R ð1;1Þ to the right-hand side and noting the tracelessness of J ð2Þ ¼ J ð1Þ ¼ 0, we obtain the reshuffled Einstein equation for the second order corrections only:…”
Section: The Nlo Stress Tensor After the Collisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second traceless condition allows us to simplify the right-hand side of Eq. (31). Moving The Ricci tensor quadratic in the first order metric R ð1;1Þ to the right-hand side and noting the tracelessness of J ð2Þ ¼ J ð1Þ ¼ 0, we obtain the reshuffled Einstein equation for the second order corrections only:…”
Section: The Nlo Stress Tensor After the Collisionmentioning
confidence: 99%
“…Such propagator has been built in various applications of AdS/CFT, e.g. [21,[28][29][30][31]. Propagators in an AdS shock wave background were found in [32,33].…”
Section: The Nlo Stress Tensor After the Collisionmentioning
confidence: 99%
“…The latter is fully determined by conformal invariance, up to an overall factor h W , which depends non-trivially on the parameters of the theory:Here |x ⊥ | generically identifies the average orthogonal distance from the location of the line defect 2 .In this paper we address the question of computing h W using supersymmetric localization. In particular, we present a derivation of the relation between h W and a small deformation of the 1 It is worth mentioning that, before the achievement of these exact results, a huge effort has been made to compute the emitted radiation at strong coupling through the AdS/CFT correspondence [5][6][7][8] 2 For a fully consistent definition see section 3.2.…”
mentioning
confidence: 99%
“…evaluated at retarded time. It depends onȧ = da/dτ , because the improved energy-momentum tensor (15) involves second derivatives of the field, and the solution depends on the velocity of the probe. In the conformal case ξ = 1/6 the terms independent or linear in the acceleration are the same as in (8), up to an overall factor.…”
Section: A Maxwell Fieldmentioning
confidence: 99%
“…At the holographic probe level, the computation of 12 , followed by 13,14 indicated that for a 1/2 BPS probe coupled to N = 4 super Yang-Mills, in the large N , large λ limit, the total radiated power is indeed of the form given by (2). The beautiful works 15,16 dealt with the backreacted holographic computations, see also [17][18][19] . The work 15 considered only a probe in circular motion, and found agreement with (2).…”
Section: Introductionmentioning
confidence: 99%